Causes, Effects, and Remedies in Conflict Management - Khan, Kamran; Hussainy, Syed Karamatullah; Iqbal, Yumna (UI Scholars Hub, 2016)
While workplace conflicts have been widely studied in the literature, this research provides a holistic view of the causes and effects of such, and how managers or a management can resolve the conflicts among their teams and organization through a detailed, multidimensional framework carried out on one of the biggest textile firms of Pakistan. With an initial sample of 145 respondents, 37 questionnaires were dropped because of invalid and incomplete answers; therefore, the study was carried out on 108 respondents. Conflicts are a part of human nature, but management should play an important role in dealing with these issues, as there can be enormous chances of conflicts due to a diverse workforce. Conflict also results in poor work performance and low productivity; therefore, it’s suggested to create teams or groups which may encourage a competitive culture in the organization. Additionally, a few remedies are identified, which may resolve some issues; managers must look at those techniques for a better culture.